Delayed Laparoscopic Repair of Bladder Injury with Vesico Cutaneous Fistula in Fracture Pelvis - Senthil Kallappan; Manickam Ramalingam; Sivasankaran Nachimuthu (Journal of Medical and Surgical Urology, 2021)
Small extra-peritoneal bladder injury is commonly treated conservatively as it heals spontaneously. However if there is an impinging bony spicule in the rent, the bladder wound does not heal and it is preferable to repair the rent primarily. We present a case of non healing extra-peritoneal bladder injury initially managed conservatively in a trauma center with supra-pubic catheter (SPC). Cystogram was done after 7 weeks showed persistent leakage of contrast. Hence patient was managed by laparoscopic repair of persistent extra-peritoneal bladder rent.
Keywords: Laparoscopic repair of Bladder injury